Association of Preoperative Anemia with Postoperative Outcomes in Patients Undergoing Gastrointestinal Surgery: A Cross-Sectional Study - Muhammad Azhar Qureshi, Adnan ur Rehman, Tahir Hamid, Rida Khan, Rafaqat Malik, S. Iftikhar Alam (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Preoperative anemia is a common clinical condition in patients undergoing gastrointestinal surgery and is associated with impaired oxygen delivery, reduced immune function, and delayed tissue healing. It is increasingly recognized as a significant predictor of adverse postoperative outcomes, particularly in resource-limited settings such as Pakistan. Aim: To assess the impact of preoperative anemia on postoperative outcomes in patients with gastrointestinal surgery. Methods: This cross-sectional study was done at Rawal Institute of Health Sciences and DHQ Teaching Hospital, from May 2022 to May 2023 involving 110 patients undergoing gastrointestinal surgery. Patients were categorized into anemic (Hb <13 g/dL in males, <12 g/dL in females) and non-anemic groups. Data on demographics, comorbidities, type of surgery, and postoperative outcomes—including surgical site infection (SSI), ICU admission, length of hospital stay, and mortality—were collected. Statistical analysis was performed using chi-square and independent t-tests, with p < 0.05 considered significant. Results: Preoperative anemia was present in 52.7% of patients. Postoperative complications were significantly higher in the anemic group, including surgical site infections (36.2% vs 13.5%, p = 0.006), ICU admissions (27.6% vs 9.6%, p = 0.01), and prolonged hospital stay (>7 days) (58.6% vs 28.8%, p = 0.002). The mean hospital stay was also significantly longer in anemic patients (8.9 ± 3.6 days vs 6.1 ± 2.8 days, p = 0.001). Although mortality was higher in anemic patients (8.6% vs 3.8%), it was not statistically significant (p = 0.28). Conclusion: Gastrointestinal surgery patients with preoperative anemia have higher post-operative morbidity. Intervention to correct anemia early may lead to better outcomes and reduced healthcare costs. Keywords: Preoperative anemia, gastrointestinal surgery, postoperative complications, surgical site infection, ICU admission, hospital stay.